2005
DOI: 10.1128/jcm.43.2.684-687.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Immunochromatographic Assay for Rapid Detection of Trichomonas vaginalis in Vaginal Specimens

Abstract: Trichomonas vaginalis infection is estimated to be the most widely prevalent nonviral sexually transmitted infection in the world. Wet-mount microscopy is the most common diagnostic method, although it is less sensitive than culture. The OSOM Trichomonas Rapid Test (Genzyme Diagnostics, Cambridge, Mass.) (referred to here as OSOM) is a new point-of-care diagnostic assay for T. vaginalis that uses an immunochromatographic capillary flow (dipstick) assay and provides results in 10 min. The purpose of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 19 publications
1
60
1
1
Order By: Relevance
“…Interestingly, women who were 36 to 45 years old had no C. trachomatis or N. gonorrhea infections but had significantly more T. vaginalis infections than women who were 16 to 25 years old (P ϭ 0.005, odds ratio [OR] ϭ 3.1, 95% confidence interval [95% CI] ϭ 1.4 to 6.6). While this statistically significant double peak is consistent with symptomatic-and asymptomatic-general-population data from our institution (7a), other studies have also shown the unique prevalence of T. vaginalis in an age group outside the recommended STI screening age groups (11,16 A total of 316 (41.3%) patient specimens were found to be positive for G. vaginalis by the Affirm assay. This seems quite high given the low prevalence of STIs in the population studied; however, all patients were symptomatic with vaginal complaints which may have selected for a more highly infected patient group.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, women who were 36 to 45 years old had no C. trachomatis or N. gonorrhea infections but had significantly more T. vaginalis infections than women who were 16 to 25 years old (P ϭ 0.005, odds ratio [OR] ϭ 3.1, 95% confidence interval [95% CI] ϭ 1.4 to 6.6). While this statistically significant double peak is consistent with symptomatic-and asymptomatic-general-population data from our institution (7a), other studies have also shown the unique prevalence of T. vaginalis in an age group outside the recommended STI screening age groups (11,16 A total of 316 (41.3%) patient specimens were found to be positive for G. vaginalis by the Affirm assay. This seems quite high given the low prevalence of STIs in the population studied; however, all patients were symptomatic with vaginal complaints which may have selected for a more highly infected patient group.…”
Section: Discussionsupporting
confidence: 88%
“…The value of our large data set also applies to age delineation of T. vaginalis detection. Past studies (11,27) showed increased T. vaginalis prevalence in older age groups but did not have the benefit of highly sensitive TMA (3,13,23). One account derived from TMA analysis (1) also reported this phenomenon but did not demonstrate C. trachomatis or N. gonorrhoeae detection in patients beyond ages 26 to 30.…”
Section: Epidemiology Of T Vaginalis In Femalesmentioning
confidence: 99%
“…It is cleared by the FDA for use on a direct vaginal swab or on used wet-mount saline. Its reported sensitivity (85 to 90%) and specificity (100%) are similar to those of culture (7,8). In addition, transcription-mediated amplification is a nucleic acid amplification test (NAAT) method that uses analyte-specific reagents for T. vaginalis.…”
mentioning
confidence: 99%